2013
DOI: 10.1063/1.4826591
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear propagation of dust-acoustic waves in an unmagnetized dusty plasma with nonthermal electron and vortex-like ion distribution

Abstract: The nonlinear propagation of dust-acoustic (DA) waves in an unmagnetized dusty plasma consisting of nonthermal electrons, vortex-like (trapped) distributed ions and mobile negative dust have been investigated by employing the reductive perturbation technique. The effects of nonthermal electrons and trapped ions are found to modify the properties of the DA solitary waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Next, for the dynamical evolution of the small-amplitude electrostatic DA perturbations we follow the same RPT as in Refs. [28,35,36]. Note that the reductive perturbation method is a very powerful way of deriving nonlinear evolution equations in simplified forms for the propagation of different kind of waves and their interactions in various nonlinear media.…”
Section: Basic Equations and The Derivation Of Kdv-like Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, for the dynamical evolution of the small-amplitude electrostatic DA perturbations we follow the same RPT as in Refs. [28,35,36]. Note that the reductive perturbation method is a very powerful way of deriving nonlinear evolution equations in simplified forms for the propagation of different kind of waves and their interactions in various nonlinear media.…”
Section: Basic Equations and The Derivation Of Kdv-like Equationmentioning
confidence: 99%
“…It was pointed out that the higher-order approximation enhances the amplitude of the DA waves [41]. Furthermore, the nonlinear propagation of DA waves has been investigated in unmagnetized dusty plasmas consisting of Boltzmannian [35] or nonthermal [36] electrons and vortex-like ions . However, no theory has been reported so far for the oblique propagation of DA waves in a magnetized dusty plasma with nonthermal electrons and trapped ions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nonthermal electrons, where the fast electrons distribution can be obtained by Vlasov equation [39], can modify linear DA waves [40] and nonlinear DA solitary waves [41] in dusty plasmas. Accordingly, in this paper we will also consider the combined effects of nonthermal electrons and trapped ions with vortex-like distribution on the properties of DA waves, which have potential application in space plasma environments [42].…”
Section: Introductionmentioning
confidence: 99%
“…The nonthermal distribution of electrons can be modeled by the Cairns distribution [44], while the distribution of free as well as trapped particles can be considered as prescribed by Schamel [45]. Accordingly the effects of nonthermal electrons [46][47][48][49][50] and trapped ions with vortex-like distribution [51][52][53][54] on the properties of electrostatic DA waves have been well studied in magnetized or unmagnetized plasma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pair-ion plasmas with positively charged dusts support DIA solitons only of the rarefactive type. There are, however, a number of recent works dealing with the nonlinear properties of solitary waves [12][13][14][15][16][17][18][19][20][21] , electrostatic ion-cyclotron waves 22 shocks 23 in other plasma environments.…”
Section: Introductionmentioning
confidence: 99%